2005
DOI: 10.1590/1808-1657v72p4452005
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Biológica E Produtiva Do Bicho-Da-Seda (Bombyx Mori L.) Alimentado Com Folhas De Amoreira Pulverizadas Com Extrato De Mirabilis Jalapa

Abstract: RESUMO O presente estudo foi realizado na Unidade de Pesquisa e Desenvolvimento de Gália, Pólo Regional de Desenvolvimento Tecnológico dos Agronegócios do Centro Oeste, em 2004, com o objetivo de avaliar a biologia e produção do bicho-da-seda quando exposto ao extrato de Mirabilis jalapa (família: Nyctaginaceae). Esse trabalho foi baseado em estudos prévios, em condições de laboratório, que mostraram a ação do extrato aquoso de Mirabilis jalapa, na concentração de 10%, sobre o controle do vírus da poliedrose (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…According to our results, the cocoon quantity (CQ) variable of the treatment i3(Vir + Bm5) was similar to that of the control groups, demonstrating that even the infected caterpillars were able to build the cocoon, similar to the results reported by Bueno et al, 2019. The larvae that were infected with BmNPV and treated with Bm5 built cocoons of good quality, presenting an average weight of 1.9 mg. Our results were also superior to those previously reported (Bhaskar et al 2011), who used different plant extracts to treat larvae infected with BmNPV and obtained average cocoon weights of 1.65 g. Higher values were also reported (Porto et al 2005), who worked on the performance of four breeds of silkworms and reported an average weight between 2.03 and 2.26 g. In Brazil, the BRATAC silk industry considers rst-class cocoons, those with an average weight of 1.9 g, which have a better selling price in the market (Sabbag et al 2013). Therefore, according to this statement, the cocoon weight (CWe) results from the Bm5 treatment presented here are considered rst-class cocoons.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…According to our results, the cocoon quantity (CQ) variable of the treatment i3(Vir + Bm5) was similar to that of the control groups, demonstrating that even the infected caterpillars were able to build the cocoon, similar to the results reported by Bueno et al, 2019. The larvae that were infected with BmNPV and treated with Bm5 built cocoons of good quality, presenting an average weight of 1.9 mg. Our results were also superior to those previously reported (Bhaskar et al 2011), who used different plant extracts to treat larvae infected with BmNPV and obtained average cocoon weights of 1.65 g. Higher values were also reported (Porto et al 2005), who worked on the performance of four breeds of silkworms and reported an average weight between 2.03 and 2.26 g. In Brazil, the BRATAC silk industry considers rst-class cocoons, those with an average weight of 1.9 g, which have a better selling price in the market (Sabbag et al 2013). Therefore, according to this statement, the cocoon weight (CWe) results from the Bm5 treatment presented here are considered rst-class cocoons.…”
Section: Discussionsupporting
confidence: 45%
“…The measurements of the biological and productive parameters were percentage of Larva LS (%) and Pupa Survival, PS (%); Cocoons Quantity, CQ; Defective Cocoons, DC; Pupa Weight in grams, PW(g); Cocoon Weight in grams, CWe(g); Cocoon Shell Weight in grams, CSW(g); Cocoon Length in millimeters, CL (mm); Cocoon Width in millimeters, CW (mm) and Silk Content percentage, SC (%). The SC (%) is derived from the formula: shell weight (g)/cocoon weight (g) x 100 − 24%, which was deducted from this value due to silk wiring loss (Porto et al, 2005).…”
Section: Assessment Of Biological and Productive Parametersmentioning
confidence: 99%
“…Identification and development of antimicrobial products to kill or inhibit microbial growth with higher efficiency but lower toxicity to animals and environmental problems are of paramount importance. In the last decade, considerable research has been done in the evaluation of plant derivatives, quaternary ammonium salts, and homeopathic and inorganic salts as antimicrobial compounds that can be used in sericulture (Porto & Okamoto, 2000;Porto et al, 2005;Hiware, 2006;Brancalhão et al, 2013;Chavan et al, 2015;Fernandes et al, 2016;Dileepkumar et al, 2018). Imidazolium salts (IS) are ionic compounds consisting of an organic cation, carrying an imidazolium ring and an organic or inorganic anion (Schrekker et al, 2008(Schrekker et al, , 2013.…”
mentioning
confidence: 99%